Domestic violence against women, family life and allegations of parental alienation - MARIA; Batista, Thais Tonini (Argumentum, 2021)
This is an introductory contribution to the literature on the “right to family life” for children and adolescents in contexts of domestic violence and on allegations of parental alienation. Based on their professional experience in the forensic arena, the authors identify the occurrence of allegations of parental alienation against women protected by restraining orders issued under the Maria da Penha Law. Based on national and international bibliographic research, the authors dialogue with the literature on domestic violence, parental alienation, and family life, making considerations on the issue of “children's best interest”, widely used in the legal system. It concludes that there have been legal and regulatory advances in the protection of the rights of the most vulnerable groups; however, the remnants of a patriarchal order are also present and reproduce gender disparities within the legal system.